Los Antepasados de A. Mickiewicz como respuesta a la cuestión de la independencia de Polonia - León Manzanero, Ana (Eslavística Complutense, 2004)
Adam Mickiewicz has a privileged place in the Polish Romanticism, and he is responsible for the main aesthetic and ideological changes of this period. The main goal of al1 his literary production is shaping a new concept of the world, man and poetry. This is especially important in the case of Dresden ForefatherslEve (1832), a work that inaugurates a decisive phase for the poet’s personal and professional sphere. Forefathers’ Eve is Mickiewicz’s answer from a messianic perspective to the problem of the loss of independence of his nation.